REPRESENTASI SERIAL TELEVISI GENDER PADA LAKI – LAKI DALAM SERIAL NETFLIX “HEARTSTOPPER”: REPRESENTASI SERIAL TELEVISI GENDER PADA LAKI – LAKI DALAM SERIAL NETFLIX “HEARTSTOPPER” - Oktavia, Luci Afiani; Rahmat, Widya (KAGANGA KOMUNIKA: Journal of Communication Science, 2024)
The words gender and sex may already be familiar to the public. But most people still often misinterpret gender as sex. Which  two very different meanings. Gender is part of the characteristics or values given by society to display different roles, traits, characters, characteristics and certain functions for men and women. Because of this, gender is considered to be inseparable from the formations and results of social construction. That men must appear and be like men who have been determined and known by society for generations, and vice versa for women. Then this gave birth to gender inequality which led to unfair treatment, compartmentalization, problems of violence, and gave rise to distinctions and social barriers between something considered normal and abnormal (deviation). The influence of the mass media has also become one of the agents in forming social construction and gender stereotypes. The presence of the internet is like being a brain that carries a variety of messages and becomes an information center with various forms of media in the form of text, audio and video. Netflix is a form of new media which is an entertainment service in the form of a streaming website and has applications on digital devices such as laptops, tablets and smartphones. Then based on the matters that have been described, this topic becomes a research to be discussed and studied. The issues that are the main focus of this research are the concepts of gender and sex, social construction of gender stereotypes and problems for men in dealing with stereotypes that cause gender bias.  Keywords : Representation Gender Stereotypes Gender Bias Masculinity  Series Heartstopper